IbM BAGI KELOMPOK BUDIDAYA JANGKRIK DI KECAMATAN SRENGAT KABUPATEN BLITAR - Haryanto Tanuwijaya; Achmad Yanu Alif Fianto; Januar Wibowo; Candraningrat . (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The purpose of this program is to develop appropriate technology (TTG)for Small Businesses in livestock crickets (ternak Jangkrik) in Pakisrejovillage, Srengat, Blitar, to minimize mortality and facilitate the mixing ofcrickets feed. The expected outcome of this program is the availability ofappropriate technologies (TTG)as a tool to minimize of the death crickets andthe availability of mixing feed machine to increase the profits and welfare offarmers crickets as partners of this program. The method used in this programwas initiated in coordination with partners to determine the necessary tools,after getting a deal then, planning and procurement TTG grinding machine feedand the engine temperature control box, then handover tools to partners.further provided training for use and maintenance tools, marketingmanagement, financial management and training in alternative processingfood-based nutrient-rich cricket and proteins, and therefore to increase salesturnover do mentoring. The results of these activities is the availability of oneset of feed grinding machine useful for softening food little crickets, milling ofcorn, soybeans, and other sentrat to mix food crickets. In addition to theactivities we purchased feed grinding machine and 21 engine temperaturecontrol box crickets useful to regulate the temperature of the box kept warm tomaintain temperature it will not too cold or not too warm which to reduce thedead of the crickets so that reduce farmers lose. After initially observed that thedeath rate of crickets in the winter season usually reach 40% but after usingthis technology to decrease become only about 3-5%.Keyword: livestock crickets, Appropriate Technology, and Business management